Feed processing parameters and their effects on nursery pig growth performance - Lewis, Landon L.; Jones, Cassandra K.; Fahrenholz, Adam C.; Goncalves, Marcio Antonio Dornelles; Stark, Charles R.; DeRouchey, Joel M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 180 nursery pigs (PIC 327 × 1050; initially 27.8 lb) were used in an 18-d study to determine the effects of conditioning parameters and feed form on pig performance. All diets were the same corn, dried distillers grains with solubles (DDGS), and soybean meal-based formulation with different processing parameters used to create the experimental treatments. Treatments included: (1) negative control mash diet, (2) positive control pelleted diet conditioned at 60 rpm, (3) pelleted diet conditioned at 30 rpm and reground, (4) pelleted diet conditioned at 60 rpm and reground, and (5) pelleted diet conditioned at 90 rpm and reground. The different rpm values among treatments represent the time in the conditioner during processing. The lower the rpm value, the longer time feed was in the conditioner. Pigs were weaned and fed a common acclimation diet for 21 d prior to the start of the experiment. Average daily gain and F/G did not differ (P > 0.12) between treatments overall, but ADFI decreased (P = 0.03) for pigs fed the pelleted, positive control diet compared with all other diets. Although no overall treatment effects were significant for ADG or F/G, the experiment was designed more specifically to evaluate treatment differences using preplanned comparisons. When considering preplanned contrasts, we observed that pigs fed mash diets tended to have greater (P = 0.10) ADG than those fed pelleted and reground diets, suggesting that processing may have had a negative influence on feed utilization, a hypothesis that is further supported because pigs fed mash diets tended to have greater (P = 0.06) ADG compared with those fed diets that were heat-processed, regardless of regrinding. Considering these results, it was not surprising that pigs fed mash diets had greater (P = 0.05) ADG and ADFI (P = 0.01) than those fed pelleted diets. When directly comparing diets conditioned at 60 rpm, fed either as whole pellets or reground to mash consistency, pigs fed pelleted diets had improved (P = 0.01) F/G due to lower ADFI (P = 0.004) but similar ADG (P = 0.60). This unexpected negative impact of pelleting on ADG may be due to a negative influence of heat treatment on palatability. The expected improvement in F/G from pelleting (6.8%) was observed but lost when diets were reground to near original mash particle size. This result may indicate that diet form (high-quality pellets vs. mash) affects F/G more than degree of starch gelatinization or other intrinsic factors associated with conditioning ingredients.
Keywords: Conditioning; Feed processing; Growth performance; Pelleting; Nursery pig